PERFORMANCE EVALUATION OF HYDROXYAPATITE PREPARED FROM EGGSHELLS IN CARBON DIOXIDE ADSORPTION - Kah Man Su,; Kiat Moon Lee,; Farihahusnah Hussin,; Mohamed Kheireddine Aroua, (Malaysian Journal of Science, 2024)
Eggshell waste is typically produced from daily poultry consumption and industrial applications. They are a rich source of calcium in the form of carbonates and oxides, recognised as excellent hydroxyapatite sources (HAp). To date, limited studies have highlighted the modification of HAp with impregnation. In the present study, HAp was prepared via the precipitation method, and further modification of HAp using monoethanolamine (MEA) and deep eutectic solvent, particularly choline chloride:urea (ChCl:U), were explored for carbon dioxide (CO2) capture. The morphological structures were studied using a scanning electron microscope, while properties were assessed using energy-dispersive X-ray spectroscopy techniques (SEM-EDX) and Brunauer-Emmett-Teller (BET). The CO2 adsorption performance using raw and impregnated HAp was also evaluated. By introducing the chemisorption process, the impregnated ChCl:U-HAp with irregular crystallite agglomerates demonstrated a higher adsorption capacity and longer breakthrough time than raw HAp and MEA-HAp. This study confirms the feasibility of using eggshells to produce HAp as an effective adsorbent in CO2 capture.